Effect of Seed Soaking with Natural Growth Regulators on Germination of Red Rice Line SF 12-2-12 - Resigia, Elara; Swasti, Etti; Putri, Nurwanita Ekasari; Kusumawati, Aries; Hasibuan, Sanna Paija (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
Rice cultivation in Indonesia involves different types of rice, including red rice, which is known to have higher nutritional value compared to white rice. However, the germination rate of red rice seeds has decreased due to poor storage conditions. Nature Growth Regulators play a critical role in the success of seed germination, seedling establishment and subsequent plant growth. To improve the quality of red rice seeds, natural growth regulators can be used. In a recent study, researchers aimed to determine the best combination of natural growth regulators and concentration level for germination of red rice line. This research was conducted from July to October 2023 at the seed technology and agronomy laboratories of the Faculty of Agriculture, Universitas Andalas. This is a factorial experiment consisting of two factors arranged in random groups design and repeated four times. The first factor was the type of natural growth regulators, namely young coconut water and shallot extract. The second factor was the concentration level, namely 0%, 35%, 70%. The data were analyzed using the F-test with a 5% level of significance. If significant differences were found, Duncan's New Multiple Range Test (DNMRT) was conducted at a 5% level. The observation parameters for the germination test carried out were the maximum growth potential (%), seed germination (%), and hard seeds (%). The application of young coconut water on concentration 70% gave the best percentage of maximum growth potential and was not different with shallot extract on concentration 70%. The application of young coconut water on concentration 70% gave the best percentage of seed germination compare to other treatment.